Focusing on the "I" in CLIL. A review of Nikula, T., Dafouz, E., Moore, P. & Smit, U. (eds.) (2016). Conceptualising Integration in CLIL and Multilingual Education. Bristol (UK): Multilingual Matters. - Hanne Roothooft (Centro Universitario Cardenal Cisneros, 2018)
Reseña del libro:   Nikula, Dafouz, E., Moore, P., & Smit, U. (2016). Conceptualising integration in CLIL and multilingual education. Multilingual Matters.